Relations, resources, and costs: exploring cross-sectoral collaboration at the local level in a developing country. Issue 5 (4th October 2021) - AbouAssi, Khaldoun; Bowman, Ann O'M.; Johnston, Jocelyn M.; Bauer, Zachary; Tran, Long
Abstract: Collaboration across sectors at the local level is seen as beneficial to both non-governmental organizations (NGOs) and local governments. Cited benefits are framed by institutional, resource dependence, and transaction cost perspectives and are often examined in a western, developed nation context. This article uses a novel sample of local governments and NGOs in Lebanon to examine whether constructs derived from these dominant theoretical frameworks explain cross-sector collaborative tendencies in the context of a developing country. We conclude that measures related to resource dependence can provide some explanatory power for collaboration behavior, but a better explanation of local government–NGO collaboration in developing countries will require reaching beyond commonly used constructs from existing dominant theories; future research toward that end is a worthwhile endeavor.